Subcellulosome preparation with high cellulase activity from Clostridium thermocellum. - Kobayashi, T (1990)
We have prepared a much simpler cellulase preparation than that of cellulosomes from the extracellular broth of Clostridium thermocellum. This "subcellulosome" preparation from C. thermocellum was obtained by column chromatography on CM-Bio-Gel A and then on a lectin-affinity material (Jacalin). The subcellulosome preparation is a macromolecular complex, composed of six main protein subunits (molecular weight, 210,000 to 58,000) revealed on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The specific activities of carboxymethylcellulase (CMCase) and Avicelase are 15- and 8-fold-higher, respectively, than those of crude extracellular cellulase. We could not further fractionate this preparation without denaturing it. The optimum pH and temperature of the subcellulosome preparation are 5.5 to 7.0 and 70 degrees C for CMCase and 5.5 to 7.0 and 65 degrees C for Avicelase. The subcellulosome preparation acted on various types of carboxymethyl cellulose, cellulose, and p-nitrophenyl-beta-D-cellobioside but not on p-nitrophenyl-beta-D-glucoside. Sulfhydryl reagents and N-bromosuccinimide inhibited both CMCase and Avicelase activities, whereas EDTA and o-phenanthroline inhibited Avicelase activity only.